Effects of dietary astaxanthin on growth performance, immunity, and tissue composition in largemouth bass, Micropterus salmoides - Zhang, Jiankun; Yang, Yeshun; Xu, Hanying; Li, Xinyu; Dong, Fen; Chen, Qiang; Han, Tao; Wang, Jiteng; Wu, Chenglong (Frontiers in Marine Science, 2024)
This study examined the effects of feeding largemouth bass (Micropterus salmoides) with diets containing different doses of astaxanthin (0, 50, 100, 150, and 200 mg/kg) for 8 weeks. The results showed that the values of weight gain significantly increased from 620.32 ± 50.38% to 826.14 ± 33.49% as dietary astaxanthin levels increased from 0 mg/kg to 100 mg/kg. When the astaxanthin level exceeded 150mg/kg, the weight gain rate showed a downward trend, but there was no significant difference among of the 100, 150 and 200 mg/kg groups. The feed conversion ratio (FCR) and protein efficiency ratio (PER) were also improved by adding astaxanthin to diets (P < 0.05). Meanwhile, adding astaxanthin to the feed increased the length and thickness of intestinal villus and muscle layer thickness (P < 0.05). The astaxanthin supplementation increased the expression of the NF-E2-related factor (Nrf2) gene and reduced malondialdehyde (MDA) content and the expression of apoptosis genes Caspase-9 and Caspase-3 (P < 0.05), indicating that it has a good antioxidant ability. Furthermore, adding astaxanthin increased the content of non-specific immune markers and decreased the expression levels of the inflammatory factors interleukin-15 (IL-15) and tumor necrosis factor-α (TNF-α). Moreover, fish fed diets with astaxanthin exhibited lower blood cortisol levels (P < 0.05). The proportions of C20:4n6 (ARA) and C20:5n3 (EPA) in the liver decreased with increasing dietary astaxanthin levels. Based on WGR and SGR values, the optimal addition level of astaxanthin in largemouth bass feed is 134.8 mg/kg ~ 135.75 mg/kg. In summary, the appropriate dietary astaxanthin enhanced the antioxidant capacity and immune response of largemouth bass and had a positive effect on its intestinal health.